THE ROLE OF LECTURE IN TEACHING THEORETICAL SUBJECTS IN BOLOGNA EDUCATION SYSTEM - Жураківська, О.Я. (World of Medicine and Biology, 2014)
The role of lecture in a credit-module system lies in the formation of students interest to the subject studying; creating a "standard of discipline"; establishing specific subject links with other clinical and theoretical disciplines; interactive character on lecture studying; express- control of training students effectiveness in the process of lecture; systematization and generalization of accumulated knowledge, formation on their basis of ideological views, beliefs of future doctor-specialist with the development of cognitive and professional interests. The lecture is designed not only to form students’ basic knowledge in a particular scientific field, but also determine the direction, content and nature of other types of classes (seminars, practical and laboratory work) and independent work. Didactic and educational lecture role is to give students a modern, holistic, interconnected knowledge level of which is determined by target setting for each particular topic.
Keywords: lecture; human anatomy; higher medical institutions